Silencing the odorant receptor co-receptor RproOrco affects the physiology and behavior of the Chagas disease vector Rhodnius prolixus. (February 2016) - Franco, Thiago A.; Oliveira, Daniele S.; Moreira, Monica F.; Leal, Walter S.; Melo, Ana C.A.
Abstract: Olfaction is one of the main sensory modalities that allow insects to interpret their environment. Several proteins, including odorant-binding proteins (OBPs) and odorant receptors (ORs), are involved in this process. Odorant receptors are ion channels formed by a binding unit OR and an odorant receptor co-receptor (Orco). The main goal of this study was to characterize the Orco gene of Rhodnius prolixus ( RproOrco) and to infer its biological functions using gene silencing. The full-length RproOrco gene sequence was downloaded from VectorBase. This gene has 7 introns and is located in the genome SuperContigGL563069 : 1, 017, 713–1, 023, 165. RproOrco encodes a protein of 473 amino acids, with predicted 7 transmembrane domains, and is highly expressed in the antennae during all R . prolixus developmental stages. The RNAi technique effectively silenced RproOrco, reducing the gene's expression by approximately 73%. Interestingly, the effect of gene silencing persisted for more than 100 days, indicating a prolonged effect of dsRNA that was maintained even after molting. The phenotypic effects of silencing involved the following: (1) loss of the ability to find a vertebrate host in a timely manner, (2) decreased ingested blood volume, (3) delayed and decreased molt rate, (4) increased mortality rate, and (5) decreased egg laying. Our data strongly suggest that dsOrco disrupts R . prolixus host-finding behavior, which is further reflected in the blood ingestion, molting, mortality, and egg laying data. This study clearly demonstrates that Orco is an excellent target for controlling triatomine populations. Thus, the data presented here open new possibilities for the control of vector-borne diseases. Graphical abstract: Highlights: RproOrco is highly expressed in the antennae of all stages of R . prolixus . The RNAi technique effectively silenced the gene in both males and females. Insects with silenced RproOrco are unable to find a vertebrate host in a timely manner. Orco silencing affects the insects' capacity to engorge on blood, decreases ecdysis and oviposition rates and increases the mortality rate. The RNAi is a powerful tool that could be applied in the control strategy for blood-sucking, disease-carrying insects.